A Practical Alternative? KardiaMobile to Improve Uptake of ECGs on Psychiatric Wards - Emily Pettifor; Faizaan Syed; Obumneme Chinweuba; Suresh Thapaliya; Mudasir Firdosi (BJPsych Open)
Aims: ECGs on psychiatric wards are crucial for detecting cardiac side effects of psychotropics and identifying patients with underlying cardiac conditions. However, there can be variable patient uptake of standard 12-lead ECGs, which can lead to delays in initiating treatment and poor quality of physical health monitoring. KardiaMobile is a portable ECG device which can offer an alternative when 12-lead ECGs have been declined by patients, and was therefore explored as a way to improve ECG uptake. The aim was to reduce delays in ECG completion for patients admitted to inpatient settings and to explore the views of patients and staff around their experience of the device.